Thermal comfort and indoor air quality analysis of a low-energy cooling windcatcher - Calautit, John Kaiser; Aquino, Angelo I.; Shahzad, Sally; Nasir, Diana S.N.M.; Hughes, Ben Richard (Elsevier, 2017)
The aim of this work was to investigate the performance of a roof-mounted cooling windcatcher integrated with heat pipes using Computational Fluid Dynamics (CFD) and field test analysis. The windcatcher model was incorporated to a 5m x 5m x3 m test room model. The study employed the CFD code FLUENT 15 with the standard k-ɛ model to conduct the steady-state RANS simulation. The numerical model provided detailed analysis of the airflow and temperature distribution inside the test room. The CO2 concentration analysis showed that the system was capable of delivering fresh air inside the space and lowering the CO2 levels. The thermal comfort was calculated using the Predicted Mean Vote (PMV) method. The PMV values ranged between +0.48 to +0.99 and the average was +0.85 (slightly warm). Field test measurements were carried out in the Ras-Al-Khaimah (RAK), UAE during the month of September. Numerical model was validated using experimental data and good agreement was observed between both methods of analysis.